2012
DOI: 10.7314/apjcp.2012.13.1.325
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between GSTM1 and GSTT1 Polymorphisms and Brain Tumour Risk

Abstract: Objective: Glutathione S-transferases (GSTs) are important enzymes that are involved in detoxification of environmental carcinogens. Molecular epidemiological studies have been conducted to investigate the association between GSTM1 and GSTT1 homozygous deletion polymorphisms and brain tumours but results have been conflicting. The aim of this study was to clarify this problem using a meta-analysis. Methods: A total of 9 records were identified by searching the PubMed and Embase databases. Fixed-and random-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…These include meta-analyses that suggest GSTM1 deficiency increases the risk of head and neck cancer (Hashibe et al, 2003;Ye et al, 2004;Tripathy and Roy, 2006), cervical cancers (Gao et al, 2011;Liu and Xu, 2012) and oral cancer ). However, a number of meta-analyses indicated no marked association of GSTM1 null mutations with hepatocellular cancer (White et al, 2008), brain tumours (Sima et al, 2012), colorectal cancers (Zhao et al, 2012), ovarian cancers (Economopoulos et al, 2010), melanoma (Nie et al, 2011). In this study, the results indicate that null GSTM1 genotype might increase susceptibility to NPC which was in accordance with the evidence-based meta-analysis pertaining to GSTM1 and GSTT1 polymorphisms on nasopharyngeal cancer by .…”
Section: Discussionsupporting
confidence: 88%
“…These include meta-analyses that suggest GSTM1 deficiency increases the risk of head and neck cancer (Hashibe et al, 2003;Ye et al, 2004;Tripathy and Roy, 2006), cervical cancers (Gao et al, 2011;Liu and Xu, 2012) and oral cancer ). However, a number of meta-analyses indicated no marked association of GSTM1 null mutations with hepatocellular cancer (White et al, 2008), brain tumours (Sima et al, 2012), colorectal cancers (Zhao et al, 2012), ovarian cancers (Economopoulos et al, 2010), melanoma (Nie et al, 2011). In this study, the results indicate that null GSTM1 genotype might increase susceptibility to NPC which was in accordance with the evidence-based meta-analysis pertaining to GSTM1 and GSTT1 polymorphisms on nasopharyngeal cancer by .…”
Section: Discussionsupporting
confidence: 88%
“…However, no strong association between GSTM1 , GSTT1 , CASP8 , XRCC1 and meningioma susceptibility was obtained. The negative associations between GSTM1 and GSTT1 null/present and meningioma risk were partly in line with previous results on the role of GSTM1 and GSTT1 polymorphisms in brain-tumor risk 10,11. In spite of this, the possibility of potential roles of these polymorphisms in inherited meningioma risk still cannot be ruled out.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, our study provided more reliable association between the rs6010620 polymorphism in RTEL1 gene and risk of glioma which resulted in more reliable conclusion. In addition, previous studies have found the association between the gene polymorphisms and glioma risk, such as the Glutathione S-transferases (GSTs) gene polymorphism (Sima et al, 2012). It may contribute to the occurrence of glioma.…”
Section: Discussionmentioning
confidence: 99%